Experimental analysis of the traffic‐induced‐vibration on an ancient lodge. Issue 3 (2nd December 2021) - Zini, Giacomo; Betti, Michele; Bartoli, Gianni
Summary: Traffic‐induced vibration is one of the main causes of small (often only cosmetic) damages for Heritage buildings. The heavy public road‐transport, often very close to these structures, may lead to fatigue phenomena due to induced continuous vibrations and consequently damages. Even if all the International Standards agree to define the velocity—expressed in terms of Peak Particle Velocity (PPV) or Peak Particle Component Velocity (PCPV)—as reference damage indicator, a standard procedure for calculating those values starting from accelerometers data is indeed absent (or needs to be better specified). This paper—taking into account that in most cases velocities cannot be directly measured—first compares the efficiency of two of the most common employed methods: the trapezoidal rule and the long Discrete Fourier Transform. This comparison is performed discussing the experimental activity performed on the SS. Annunziata's lodge in Florence (Italy) which is particularly exposed to traffic‐induced vibrations. Subsequently, a systematic analysis of the traffic‐induced vibration phenomenon was performed based on (i) dynamic identification by means of accelerometers data; (ii) calculation of the velocities (PPV and PCPV); (iii) analysis of the traffic component effects; and (iv) analysis of the Structure‐Soil Interaction (SSI) by using results obtained by means of Falling Weight Tests (FWT). Eventually, a comparison with the results of a previous dynamic test campaign performed in 1994 is reported, underlining a consistent increase of the traffic‐induced vibrations on the lodge possibly caused by the increase of the road unevenness.